2019
DOI: 10.1038/s41418-019-0457-8
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis is dispensable for motor neuron degeneration in a mouse model of ALS

Abstract: Motor neuron degeneration in amyotrophic lateral sclerosis (ALS) is proposed to occur by necroptosis, an inflammatory form of regulated cell death. Prior studies implicated necroptosis in ALS based on accumulation of necroptotic markers in affected tissues of patients and mouse models, and amelioration of disease in mutant superoxide dismutase 1 (SOD1 G93A ) mice with inhibition of the upstream necroptotic mediators, receptor interacting protein kinase 1 (RIPK1), and RIPK3. To definitively address the pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 42 publications
(81 reference statements)
5
46
1
Order By: Relevance
“…A role for necroptosis signalling in ALS has also been proposed as pharmacological inhibition or genetic ablation of RIPK1 delayed symptom onset in the SOD1 G93A mouse model [ 144 ]. However, subsequent studies have questioned the role of necroptosis in ALS as neither a kinase dead mutant of RIPK1 [ 145 ], nor deletion of MLKL [ 146 ], delayed disease progression in the same mouse model.…”
Section: Ubiquitin Signalling In Neuronal Cell Deathmentioning
confidence: 99%
“…A role for necroptosis signalling in ALS has also been proposed as pharmacological inhibition or genetic ablation of RIPK1 delayed symptom onset in the SOD1 G93A mouse model [ 144 ]. However, subsequent studies have questioned the role of necroptosis in ALS as neither a kinase dead mutant of RIPK1 [ 145 ], nor deletion of MLKL [ 146 ], delayed disease progression in the same mouse model.…”
Section: Ubiquitin Signalling In Neuronal Cell Deathmentioning
confidence: 99%
“…[55,56]). Consequently, errant necroptosis has been implicated in the pathology of inflammatory syndromes [57], atherosclerosis [58], cardiac [59] and kidney [60] ischemia/reperfusion injury, sepsis [61][62][63], inflammatory bowel disease [64], neurodegenerative diseases [65], and cancer [66], although some of these attributions remain the matter of debate [62,[67][68][69][70][71][72]. In addition, damage caused by some bacterial infections have been proposed to be attributable to excessive necroptosis and inflammation [73,74].…”
Section: Therapeutic Targeting Of Necroptosis In Human Diseasementioning
confidence: 99%
“…The role of necroptosis in ALS remains controversial, as motor neuron disease in murine models is independent of necroptosis signaling and MLKL activation [99,100]. In contrast, recent in vitro work using a fully-humanized co-culture system demonstrated that an unidentified toxic factor secreted from primary astrocytes from sporadic ALS, but not those from control patients, triggered necroptosis-mediated death of motor neurons [69].…”
Section: Discussionmentioning
confidence: 99%